If it's not what You are looking for type in the equation solver your own equation and let us solve it.
=-2Y(Y-150)
We move all terms to the left:
-(-2Y(Y-150))=0
We calculate terms in parentheses: -(-2Y(Y-150)), so:We get rid of parentheses
-2Y(Y-150)
We multiply parentheses
-2Y^2+300Y
Back to the equation:
-(-2Y^2+300Y)
2Y^2-300Y=0
a = 2; b = -300; c = 0;
Δ = b2-4ac
Δ = -3002-4·2·0
Δ = 90000
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$Y_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$Y_{2}=\frac{-b+\sqrt{\Delta}}{2a}$$\sqrt{\Delta}=\sqrt{90000}=300$$Y_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-300)-300}{2*2}=\frac{0}{4} =0 $$Y_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-300)+300}{2*2}=\frac{600}{4} =150 $
| X+.20x=1,450 | | (4x)-3x=-6 | | 44=11x+11 | | (5y-65)+75=180 | | (n+5)/5=35 | | 6x+12=2+3x-27 | | 2.5x+2.5=10x= | | 5x+25=-2(x-4) | | 100=900-100w | | 128+x+65=180 | | -54-4x-2x=60 | | 3x=4=9x-8 | | 63+45+x=90 | | 61+(5z-94)=180 | | 9x+3(4+x)=0 | | |−2x+2|=|4x−4| | | -(-4x-2)-8x+6=32 | | 5x+40=40x= | | 3/2x+1-2/x-4=0 | | 4+6y=9+6y | | -13-5x+7x=15 | | 108=12h | | 6x+12=3x-25 | | (3x+9)=90 | | t-3(4-t)=-21 | | 3x-9=2x-9+2x | | -95+7x-x=31 | | +4x-86x+4-2=10 | | X+3+53=x | | 3x+5=7x= | | 17x+5+51+90=18 | | 2x-70-8x=56 |